Tolerance of Placozoa for temperate climates: Evidence for known and new placozoan clades in the southern waters of Australia - Bree A. Wright; Hans-Jürgen Osigus; Moritz J. Schmidt; Julian Ratcliffe; Kai Kamm; Gabriela C. Martinez-Ortiz; Martina Rehn; Marc Kvansakul; Bernd Schierwater; Patrick O. Humbert (PLoS ONE, 2025)
Placozoans are small multicellular sea-dwelling animals that are typically found in shallow, warm ocean waters and have been reported in various marine environments worldwide. Their unique morphology makes them a powerful new model organism to study the evolutionary cell biology in early metazoans. Yet, knowledge on their biodiversity and ecological distribution is severely limited. Here, we report the isolation of placozoans in the temperate waters of Victoria, Australia, their most southern location known to date. Using light, electron, and confocal microscopy, we describe their morphology and behaviour. In addition to the known haplotypes H2 and H17, we have identified a new haplotype, here designated as H20, which defines a new placozoan clade. This study provides novel insights into the distribution, ecological niche separation and genetic diversity of placozoans, and reports the first morphological and ultrastructural characterisation of placozoan clades isolated from the southern waters of Victoria, Australia.